1994
DOI: 10.1111/j.1745-4557.1994.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of ‘Climax’ Blueberries After Low Dosage Electron Beam Irradiation

Abstract: Fruit of 'Climax' rabbiteye blueberries (Vaccinium ashei Reade) were irradiated by a linear accelerator at 0, 0.25, 0.5, 0.75, 1.0, and 1.25 kGy and evaluated for various quality attributes after storage for 1, 3, 7, or 14 days at ICpEus 2 days at 15C, respectively. Weight loss increased during storage and averaged 4.2 % after the final inspection and was not affected by irradiation dosage. About 5 % of total berries were decayed after 14 days at 1 C, about 6 % after the final inspection at 15C, but decay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
2
19
0
2
Order By: Relevance
“…In our study, however, 0.4 kGy did not lower mold counts as compared to the control suggesting that the D values for these organisms on cherries is higher than 0.4 kGy. In fact, Jeong and colleagues determined D values for pure cultures to be between 3 and 4 kGy for B. cinerea and 1 and 2 kGy for P. expansum and R. stolonifera and several studies show that decay in blueberries is not impacted even at 3.0 kGy . Drake and Neven saw increased defects and softening in Bing cherries irradiated at 0.9 kGy so it is likely that at the doses required for significant mold reduction, quality may be compromised.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, however, 0.4 kGy did not lower mold counts as compared to the control suggesting that the D values for these organisms on cherries is higher than 0.4 kGy. In fact, Jeong and colleagues determined D values for pure cultures to be between 3 and 4 kGy for B. cinerea and 1 and 2 kGy for P. expansum and R. stolonifera and several studies show that decay in blueberries is not impacted even at 3.0 kGy . Drake and Neven saw increased defects and softening in Bing cherries irradiated at 0.9 kGy so it is likely that at the doses required for significant mold reduction, quality may be compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, raspberries treated with 1.5 kGy gamma radiation reduced microbial load, but with effects on firmness, phenolic content, and antioxidant capacity during storage (Cabo Verde et al, 2013). Studies on the qualities of various types of blueberries receiving doses above 1 kGy reported decreases in ascorbic acid content (Moreno et al, 2008) and decreases in berry firmness Miller et al, 1994), but the berries were not necessarily deemed unacceptable. Higher doses up to 3.2 kGy are reported to affect flavor and color of blueberries (Morena et al, 2007).…”
Section: Contamination Reduction Strategiesmentioning
confidence: 99%
“…Irradiation has been reported to extend the shelf-life of berries, but effects on quality depend on the berry type and dosage. Studies on the qualities of various types of blueberries receiving doses above 1 kGy reported decreases in ascorbic acid content (Moreno et al, 2008) and decreases in berry firmness (Moreno et al, 2007;Miller et al, 1994), but the berries were not necessarily deemed unacceptable. Similarly, raspberries treated with 1.5 kGy gamma radiation reduced microbial load, but with effects on firmness, phenolic content, and antioxidant capacity during storage (Cabo Verde et al, 2013).…”
Section: Contamination Reduction Strategiesmentioning
confidence: 99%